2014
DOI: 10.1590/0031-1049.2014.54.06
|View full text |Cite
|
Sign up to set email alerts
|

The orchid bees (Hymenoptera, Apidae, Euglossina) in a forest fragment from western Paraná state, Brazil

Abstract: The orchid bees (hymenopTera, apidae, euglossina) in a foresT fragmenT from wesTern paraná sTaTe, brazil rodrigo b. gonçalves 1,2 vanessa l. scherer 1 priscila s. oliveira 1 absTracT An orchid bee inventory was carried out in Parque Estadual São Camilo, Palotina, Paraná (Brazil); conservation unit with about 400 hectares of Semidecidual Seasonal forest. Three bait traps were installed at the border of the fragment, each one containing the following fragrances: 1,8-cineole, eugenol, and vanilin. Sampling was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 21 publications
3
21
1
1
Order By: Relevance
“…Regarding the newly sampled sites (C and D), the orchid bee richness was similar to results found in the other areas, as Gonçalves et al (2014b) (Guérin, 1844). Richness and abundance of orchid bees in southern Atlantic forests are smaller than those from the northern Atlantic and Amazonian forests, what had already been shown by the negative correlation of orchid bees and the Neotropical latitudinal gradient of species richness (Sydney et al, 2010).…”
Section: Local Faunassupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding the newly sampled sites (C and D), the orchid bee richness was similar to results found in the other areas, as Gonçalves et al (2014b) (Guérin, 1844). Richness and abundance of orchid bees in southern Atlantic forests are smaller than those from the northern Atlantic and Amazonian forests, what had already been shown by the negative correlation of orchid bees and the Neotropical latitudinal gradient of species richness (Sydney et al, 2010).…”
Section: Local Faunassupporting
confidence: 78%
“…Sites A-C are fragments in a soybean and corn crop matrix, while site D is a fragment inside the urban area of Palotina, a small city with 31,564 inhabitants (IBGE, 2018). Detailed information regarding sites A and B are presented in Gonçalves et al (2014b) and Gonçalves et al (2014a), respectively.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…Recently, Ferronato et al (2017) investigated the Euglossini community in native and reforested forests and they observed that some species of orchid bees seem to indicate a better quality of habitat, besides the possible reintegration of the bee community from the reforested forests being favored by native forest. Although studies comparing the richness and abundance of Euglossini among several forest fragments are not scarce Aguiar et al, 2014;Gonçalves et al, 2014;Giangarelli et al, 2015;Ferronato et al, 2017), very little is known about the distribution of these species in microenvironments, mainly comparing the micro-environments mosaic within the primary and secondary forest and if the distribution of the species affect the attractiveness of the essences in these different micro-environments.…”
Section: Discussionmentioning
confidence: 99%
“…diversity of orchid bees at multiple scales (ecological and molecular level) are common in the Neotropical region (Raw, 1989;Silveira et al, 2011;Boff et al, 2014;Gonçalves et al, 2014;Eltz et al, 2015;Giangarelli et al, 2015;Penha et al, 2015;McCravy et al, 2016) because orchid bee males are easily attracted to chemical compounds (Dodson et al, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation